The Updated Role of Transcranial Ultrasound Neuromodulation in Ischemic Stroke: From Clinical and Basic Research - Zhu, Shuiping; Meng, Bin; Jiang, Jianping; Wang, Xiaotao; Luo, Na; Liu, Ning; Shen, Huaping; Wang, Lu; Li, Qian (Frontiers in Cellular Neuroscience, 2022)
Ischemic stroke is a common cause of death and disability worldwide, which leads to serious neurological and physical dysfunction and results in heavy economic and social burdens. For now, timely and effective dissolution of thrombus, and ultimately improvement in the recovery of neurological functions, is the treatment strategy focus. Recently, many studies have reported that transcranial ultrasound stimulation (TUS), as a non-invasive method, can dissolve thrombus, improve cerebral blood circulation, and exert a neuroprotective effect post-stroke. TUS can promote functional recovery and improve rehabilitation efficacy among ischemic stroke patients. This mini review summarizes the potential mechanism and limitation of TUS in stroke aims to provide a new strategy for the future treatment of ischemic stroke patients.